2018
DOI: 10.1007/s00216-018-0964-3
|View full text |Cite
|
Sign up to set email alerts
|

MALDI imaging facilitates new topical drug development process by determining quantitative skin distribution profiles

Abstract: Generation of skin distribution profiles and reliable determination of drug molecule concentration in the target region are crucial during the development process of topical products for treatment of skin diseases like psoriasis and atopic dermatitis. Imaging techniques like mass spectrometric imaging (MSI) offer sufficient spatial resolution to generate meaningful distribution profiles of a drug molecule across a skin section. In this study, we use matrix-assisted laser desorption/ionization mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…Leo-29102 was developed by Leo Pharma in 2014, and it acts as a potent and selective PDE4 inhibitor with excellent anti-inflammatory properties (Felding et al, 2014 ; Bonnel et al, 2018 ). By this point, a phase II study with Leo-29102 had been launched, and the study intended to observe the clinically relevant efficacy of the drug in treating AD.…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%
“…Leo-29102 was developed by Leo Pharma in 2014, and it acts as a potent and selective PDE4 inhibitor with excellent anti-inflammatory properties (Felding et al, 2014 ; Bonnel et al, 2018 ). By this point, a phase II study with Leo-29102 had been launched, and the study intended to observe the clinically relevant efficacy of the drug in treating AD.…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%
“…Some examples of regional distribution analysis of simultaneously dosed drugs, or cassette dosing, have been highlighted by MSI. (15)(16)(17)(18) For instance, Swales et al (17) showed that multimodal MSI enables the detection of four drugs (Moxifloxacin, Olanzapine, Erlotinib, and Terfenadine) in the same organs (kidney and liver). Data of this type are important in the scope of 3Rs (replace, reduce, or refine the use of animals in research) and can help compound optimization in preclinical drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…This observation indicates that TFV-DP may have been less readily detectable in the colorectal tissue biopsies owing to the ability of TFV-DP to form stronger interactions with endogenous cellular components than does TFV. Of note, it has been reported that there is a correlation between the MALDI MSI sensitivity and analyte lipophilicity (Log P value) (Bonnel et al, 2018). Therefore, the observed relationship between Log P values of TFV and TFV-DP and their differential detection in tissue reveals a potential factor that could contribute to the observed TFV and TFV-DP distributions in tissue.…”
Section: Discussionmentioning
confidence: 79%
“…Tissue extinction coefficient (TEC) values were calculated by dividing the relative ion abundance of TFV (or TFV-DP) in tissue (BioreclamationIVT, Baltimore, MD) by the relative ion abundance of TFV (or TFV-DP) when spotted directly onto a slide using a mixture of TFV and TFV-DP (50 mM) as previously described (Bonnel et al, 2018).…”
Section: Methodsmentioning
confidence: 99%